Recombinant human interferon gamma (Gamma Immunex) in treatment of atopic dermatitis - Panahi, Yunes; Davoudi, Seyyed Masoud; Madanchi, Nima; Abolhasani, Ehsan (Clinical and experimental medicine, 2012)
Atopic dermatitis (AD) is a chronic, inflammatory skin disease which is characterized by severe pruritus and affects patients’ quality of life. In recent years gamma interferon (IFN-gamma) has been accepted as a novel treatment for severe AD, however, its mechanism of action is not clearly identified. Present study evaluated the effect of recombinant human interferon gamma (rIFN-gamma: Gamma Immunex, Exir Pharmaceutical Company, Iran) on severity of AD (SCORAD), dermatology life quality index (DLQI) as well as serum levels of IL-4, IgE and IL-6 in AD patients. Twenty AD patients were entered in to a study in Baqiyatallah outpatient clinics and received rIFN-gamma (50 μg/m 2 body area, 3 times per week, subcutaneously) for 1 month. SCORAD and DLQI were assessed at beginning and end of the treatment period. IL-4, IL-6 and IgE were measured in blood samples before and after 1 month treatment with rIFN-gamma. DLQI mean value before treatment was 20.80 ± 3.95, which decreased to 8.20 ± 2.14 after treatment ( P < 0.001). SCORAD-A (percentile of the body surface involved in AD), SCORAD-B (the severity of clinical features) and SCORAD-C (patients’ scaling of itching and somnolence) significantly decreased after treatment ( P < 0.001, P < 0.001 and P < 0.01). Total SCORAD at the end of treatment period was less than basal value (27.83 ± 8.48 vs. 70.04 ± 8.48; P < 0.001). Treatment with rIFN-gamma decreased serum levels of IL-4 and IL-6 ( P < 0.05), but IgE remained unchanged. Results suggested the controlling effect of rIFN-gamma treatment on clinical symptoms of AD, which involves suppression of IL-4 but not IgE production.